The survival and function of IL-10-producing regulatory B cells are negatively controlled by SLAMF5 - Lihi Radomir; Matthias P. Kramer; Michal Perpinial; Nofar Schottlender; Stav Rabani; Keren David; Anna Wiener; Hadas Lewinsky; Shirly Becker-Herman; Rina Aharoni; Ron Milo; Claudia Mauri; et al. (Nature Communications, 2021)
Regulatory B (Breg) cells suppress excessive inflammation primary via the production of interleukin 10 (IL-10). Here the authors show that the function and homeostasis of mouse and human IL-10+ Breg cells are negatively regulated by the cell surface receptor, SLAMF5, to impact experimental autoimmunity, thereby hinting SLAMF5 as a potential target for immunotherapy.